Differentiation of prostatitis and prostate cancer using the Prostate Imaging—Reporting and Data System (PI-RADS). Issue 7 (July 2016) - Meier-Schroers, Michael; Kukuk, Guido; Wolter, Karsten; Decker, Georges; Fischer, Stefan; Marx, Christian; Traeber, Frank; Sprinkart, Alois Martin; Block, Wolfgang; Schild, Hans Heinz; Willinek, Winfried
Highlights: Prostatitis can be differentiated from prostate cancer using PI-RADS, but there is significant overlap between prostatitis and other benign findings. Prostatitis is believed to have restricted diffusion with ADC-values ≥ 900 mm 2 /s. Borderline pathological PI-RADS scores, indistinct T2-hypointensity, and localization in the transitional zone are other characteristics that seem to make prostatitis probable. MRS can help to distinguish between prostatitis and other tissue. Abstract: Purpose: To determine if prostate cancer (PCa) and prostatitis can be differentiated by using PI-RADS. Materials and methods: 3T MR images of 68 patients with 85 cancer suspicious lesions were analyzed. The findings were correlated with histopathology. T2w imaging (T2WI), diffusion weighted imaging (DWI), dynamic contrast enhancement (DCE), and MR-Spectroscopy (MRS) were acquired. Every lesion was given a single PI-RADS score for each parameter, as well as a sum score and a PI-RADS v2 score. Furthermore, T2-morphology, ADC-value, perfusion type, citrate/choline-level, and localization were evaluated. Results: 44 of 85 lesions showed PCa (51.8%), 21 chronic prostatitis (24.7%), and 20 other benign tissue such as hyperplasia or fibromuscular tissue (23.5%). The single PI-RADS score for T2WI, DWI, DCE, as well as the aggregated score including and not including MRS, and the PI-RADS v2-score were all significantly higher for PCa than for prostatitis or other tissue (p < 0.001). The single PI-RADS score for MRS and the PI-RADS sum score including MRS were significantly higher for prostatitis than for other tissue (p = 0.029 and p = 0.020), whereas the other parameters were not different. Prostatitis usually presented borderline pathological PI-RADS scores, showed restricted diffusion with ADC ≥ 900 mm 2 /s in 100% of cases, was more often indistinctly hypointense on T2WI (66.7%), and localized in the transitional zone (57.1%). An ADC ≥ 900 mm 2 /s achieved the highest predictive value for prostatitis (AUC = 0.859). Conclusion: Prostatitis can be differentiated from PCa using PI-RADS, since all available parameters are more distinct in cases of cancer. However, there is significant overlap between prostatitis and other benign findings, thus PI-RADS is only suitable to a limited extent for the primary assessment of prostatitis. Restricted diffusion with ADC ≥ 900 mm 2 /s is believed to be a good indicator for prostatitis. MRS can help to distinguish between prostatitis and other tissue.